Occurrences of the brown colour form of Western Whip (Hierophis viridiflavus carbonarius (Bonaparte, 1833)) in Slovenia - Tomaž Jagar; Erika Ostanek (Natura Sloveniae)
This article presents the first documented records of brown coloured adults of Hierophis viridiflavus carbonarius in Slovenia, and overviews some of the historical notes on unconfirmed sightings of Hierophis gemonensis in the same area of distribution.